2019
DOI: 10.5981/jjhnc.45.1
|View full text |Cite
|
Sign up to set email alerts
|

Depth of invasion(DOI) introduced in UICC 8th T classification in tongue carcinoma

Abstract: To clarify the problem of the new T classification in tongue carcinoma, we reviewed the records of 427 previously untreated tongue cancer patients between 2006 and 2015. In the 7 th edition, there were 224 patients in T1, 152 in T2, 42 in T3, and 9 in T4a. In the 8 th edition, there were 204 patients in T1, 149 in T2, and 74 in T3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first study on MRI divided into “before biopsy” and “after incision biopsy”. Our prior study focusing on the period between 2006 and 2015 showed that r-DOI using MRI before biopsy best correlated with p-DOI 26 . The present study expanded on this by including a larger patient number and considering the width shrinkage rate during the preparation process of histopathological specimen.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, this is the first study on MRI divided into “before biopsy” and “after incision biopsy”. Our prior study focusing on the period between 2006 and 2015 showed that r-DOI using MRI before biopsy best correlated with p-DOI 26 . The present study expanded on this by including a larger patient number and considering the width shrinkage rate during the preparation process of histopathological specimen.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the cutoff values of the pDOI for cervical lymph node metastases vary from 3 mm [46] to 6 [47] mm. Because the specimen contraction rate at the time of pathological specimen preparation differs among institutions [48,49], establishing a standard is difficult. In this study, we found that the mean clinical tumor thickness was 3.9 mm, but the mean pathological tumor thickness of the resected tumors (n = 61) was 3.4 mm, indicating a mean difference of approximately 13% between the clinical and pathological findings.…”
Section: Discussionmentioning
confidence: 99%